\(\begin{array}{l}f'\left( {{x_0}} \right) = \mathop {\lim }\limits_{x \to {x_0}} \frac{{f(x) - f\left( {{x_0}} \right)}}{{x - {x_0}}} = \mathop {\lim }\limits_{x \to {x_0}} \frac{{\ln x - \ln {x_0}}}{{x - {x_0}}} = \mathop {\lim }\limits_{x \to {x_0}} \frac{{\ln \frac{x}{{{x_0}}}}}{{x - {x_0}}} = \mathop {\lim }\limits_{x \to {x_0}} \frac{{\frac{{\ln \frac{x}{{{x_0}}}}}{{\ln e}}}}{{x - {x_0}}} = \frac{1}{{\ln e}}.\mathop {\lim }\limits_{x \to {x_0}} \frac{{\ln \frac{x}{{{x_0}}}}}{{x - {x_0}}}\\ = \frac{1}{{\ln e}}\mathop {\lim }\limits_{x \to {x_0}} \frac{{\ln \left( {1 + \frac{x}{{{x_0}}} - 1} \right)}}{{x - {x_0}}} = \frac{1}{{\ln e}}\mathop {\lim }\limits_{x \to {x_0}} \frac{{\frac{x}{{{x_0}}} - 1}}{{x - {x_0}}} = \frac{1}{{\ln e}}.\mathop {\lim }\limits_{u \to 0} \frac{{\frac{{x - {x_0}}}{{{x_0}}}}}{{x - {x_0}}} = \frac{1}{{{x_0}\ln e}}\\ \Rightarrow \left( {\ln x} \right)' = \frac{1}{{x\ln e}} = \frac{1}{x}\end{array}\)